(3 5/6-2/6)+4 2 1/7+ ( 4/7+1 2/7) 6 2/5- (1 3/5 - 1/5) ( 3 7/8+1/8)- 2 5/8 7\9 + ( 1 2/9 - 5/9) ( 4 2/5 + 4/5) + 1 4/5 6 1/4 - ( 3 2/4 + 1 1/4) ( 5 - 2 3/8) - 7/8

nick121201 nick121201    1   29.05.2019 22:10    1

Ответы
tel9057969295p0bj7i tel9057969295p0bj7i  29.06.2020 12:10
(3 5/6-2/6)+4= 3 3/6 + 4= 7 1/2
2 1/7+ ( 4/7+1 2/7)= 2 1/7 + 1 6/7=4
6 2/5- (1 3/5 - 1/5)= 6 2/5 - 1 2/5=5
( 3 7/8+1/8)- 2 5/8 = 4 - 2 5/8=1 3/8
7\9 + ( 1 2/9 - 5/9)= 7/9 + 6/9= 13/9=1 4/9
( 4 2/5 + 4/5) + 1 4/5= 5 1/5+ 1 4/5=7
6 1/4 - ( 3 2/4 + 1 1/4)= 6 1/4 - 4 3/4= 1 1/2
( 5 - 2 3/8) - 7/8= 2 5\8- 7/8= 1 6/8= 1 3/4
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика